Wahidin Dakwah Preneurship 5.0: Model Inkubasi Bisnis Dalam Pengembangan Inovasi Lembaga Dakwah (Studi Pada Dompet Dhuafa Dan Masjid Jogokariyan)” - Wahidin Wahidin, S. Sos (Mudabbir: Jurnal Manajemen Dakwah, 2025)
This study examines the Dakwahpreneurship 5.0 model as an innovation in Islamic missionary institutions through faith-based business incubation. The research focuses on two key case studies Dompet Dhuafa and Jogokariyan Mosque which represent two distinct approaches to Muslim community economic empowerment. The central problem addressed is how spiritual values, institutional structure, and community strength can be integrated into a coherent model of faith-based business incubation. Using a qualitative approach and library research methods, this study analyzes relevant literature, institutional reports, and recent academic publications. The findings reveal that Dompet Dhuafa employs a professional, structured incubation model, while Jogokariyan Mosque adopts an organic, community-driven model rooted in gotong royong (collective solidarity). Both share the same orientation toward social justice and communal welfare, yet differ in scalability and governance systems. The study formulates the conceptual framework of Dakwahpreneurship 5.0, emphasizing the integration of managerial professionalism, Islamic spirituality, and community engagement as the foundation for sustainable faith-based economic development in the digital era. This model serves as a strategic reference for Islamic institutions seeking to develop equitable, adaptive, and transformative economic empowerment systems